Fashion Sebagai Alat Diplomasi Negara: Menganalisis Pengaruh Industri Fashion Prancis Terhadap Diplomasi Publik** - Anggrein, Fiorentina (Jurnal Ilmiah Wahana Pendidikan, 2025)
Fashion is indeed considered a significant aspect of French culture and is often associated with the national branding of France. The country has a rich history and tradition in the world of fashion, and French fashion designers, brands, and styles have had a profound influence on the global fashion industry. This research aims to look at how influential the fashion industry is on French public diplomacy. In compiling this research, the authors used qualitative research methods and used data collection methods from the library research. It involves exploring existing literature, published materials, and academic sources to gain insights, support arguments, and develop a comprehensive understanding of a particular topic. The fashion industry in France has long been recognized as a significant component of the country’s cultural and creative identity. It plays a crucial role in promoting public diplomacy, which refers to the use of cultural, educational, and informational resources to build relationships, shape perceptions, and enhance a nation’s reputation on the global stage. Through its cultural diplomacy efforts, it serves as a tool for soft power projection.